2004
DOI: 10.1111/j.1471-4159.2004.02874.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, localization and circadian expression of chicken melanopsin (Opn4): differential regulation of expression in pineal and retinal cell types

Abstract: The avian retina and pineal gland contain autonomous circadian oscillators and photo-entrainment pathways, but the photopigment(s) that mediate entrainment have not been definitively identified. Melanopsin (Opn4) is a novel opsin involved in entrainment of circadian rhythms in mammals. Here, we report the cDNA cloning of chicken melanopsin and show its expression in retina, brain and pineal gland. Like the melanopsins identified in amphibians and mammals, chicken melanopsin is more similar to the invertebrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
0
18

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(178 citation statements)
references
References 69 publications
(145 reference statements)
5
155
0
18
Order By: Relevance
“…The nucleotide sequence of cOpn4-a was identical to the one deposited in GenBank (accession number, AY036061; Chaurasia et al, 2005), encoding a 543-amino-acid protein (Fig. 1B).…”
Section: Two Types Of Chicken Melanopsin Mrna Are Expressed During Dementioning
confidence: 88%
“…The nucleotide sequence of cOpn4-a was identical to the one deposited in GenBank (accession number, AY036061; Chaurasia et al, 2005), encoding a 543-amino-acid protein (Fig. 1B).…”
Section: Two Types Of Chicken Melanopsin Mrna Are Expressed During Dementioning
confidence: 88%
“…Although rhodopsin-like immunoreactivity has been observed in the pigeon septal region (11,12), multiple independent studies failed to detect similar signals in the quail brain (13,14). Expression of melanopsin has been demonstrated in the lateral septal region as well as the retina and pineal gland in chicks (15). Recently, vertebrate ancient (VA) opsin-like immunoreactivity was detected in the avian anterior hypothalamus (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude the possibility that some of the chicken probes did not work in quail. In addition, it is reported that expression of some opsin genes is rhythmically regulated (15,41). Because we collected brains in the middle of the day, the expression of some genes may have been too low for detection at that time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other opsin genes are also expressed with a strong daily rhythm [6][7][8]13,17,[23][24][25]29,31,33,35,42,49,50,55,59]. However, the function of this rhythmic expression is not well understood.…”
Section: The Pattern Of Exorh Transcription Is Controlled By a Combinmentioning
confidence: 99%